2020
DOI: 10.1007/s00354-020-00108-w
|View full text |Cite
|
Sign up to set email alerts
|

Bisociative Literature-Based Discovery: Lessons Learned and New Word Embedding Approach

Abstract: The field of bisociative literature-based discovery aims at mining scientific literature to reveal yet uncovered connections between different fields of specialization. This paper outlines several outlier-based literature mining approaches to bridging term detection and the lessons learned from selected biomedical literature-based discovery applications. The paper addresses also new prospects in bisociative literature-based discovery, proposing an advanced embeddings-based technology for cross-domain literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Broadly, however, we aim for annotators to rate structural/relational similarities between the candidate and query higher (3-2 ratings) than attribute/feature based similarities (1-0 ratings). This draws on motivations from a range of literature highlighting the value of structural similarities to creative activities like scientific research -a focus of this work [8,15,30,33]. While we refer readers to our annotator guidelines for detailed instructions for the relevance grades, we present a summary of the highest grade by facet as an illustration here: background: +3 implies that both papers are trying to accomplish the same specific goal, are solving the same specific modeling problem or the same machine learning task, or are motivated in a specific similar manner.…”
Section: Relevance Ratingsmentioning
confidence: 99%
“…Broadly, however, we aim for annotators to rate structural/relational similarities between the candidate and query higher (3-2 ratings) than attribute/feature based similarities (1-0 ratings). This draws on motivations from a range of literature highlighting the value of structural similarities to creative activities like scientific research -a focus of this work [8,15,30,33]. While we refer readers to our annotator guidelines for detailed instructions for the relevance grades, we present a summary of the highest grade by facet as an illustration here: background: +3 implies that both papers are trying to accomplish the same specific goal, are solving the same specific modeling problem or the same machine learning task, or are motivated in a specific similar manner.…”
Section: Relevance Ratingsmentioning
confidence: 99%
“…Arthur Koestler considered bisociation to be the foundation of human creativity in science and art. He also thought that bisocial thinking occurs when a problem is perceived simultaneously in two or more different domains [7]. Figure 7 presents an example of bisociative network.…”
Section: Bisociative Information Networkmentioning
confidence: 99%
“…A study by Tshitoyan et al (2019) showed that latent knowledge regarding future discoveries is to a large extent embedded in past publications by retrieving information from the scientific literature with the usage of word2vec embeddings (Mikolov et al, 2013). The recent approach by Lavrač et al (2020) explored how word embeddings (Joulin et al, 2016) can be used for identification of novel bridging terms in the field of plant biology. A similar approach was also explored in the context of COVID-19-related biomarker discovery (Martinc et al, 2020).…”
Section: Introductionmentioning
confidence: 99%